The efficacy and safety of using cooled radiofrequency in treating chronic sacroiliac joint pain: A PRISMA-compliant meta-analysis. Issue 6 (February 2018) - Sun, Hui-Hui; Zhuang, Su-Yang; Hong, Xin; Xie, Xin-Hui; Zhu, Lei; Wu, Xiao-Tao
Abstract: Background: Cooled radiofrequency procedure is a novel minimally invasive surgical technique and has been occasionally utilized in managing chronic sacroiliac joint (SIJ) pain. A meta-analysis was conducted to systematically assess the efficacy and safety of using cooled radiofrequency in treating patients with chronic SIJ pain in terms of pain and disability relief, patients' satisfaction degree as well as complications. Methods: Studies of using cooled radiofrequency procedure in managing SIJ pain were retrieved from Medline and Web of Science according to inclusion and exclusion criteria. Quality evaluation was conducted using Cochrane collaboration tool for randomized controlled trials and MINORS quality assessment for noncomparative trials. Statistics were managed using Review Manager 5.3. Results: Totally 7 studies with 240 eligible patients were enrolled. The overall pooled results demonstrated that pain intensity decreased significantly after cooled radiofrequency procedure compared with that measured before treatment. The mean difference (MD) was 3.81 [95% confidence intervals (95% CIs): 3.29–4.33, P < .001] and 3.78 (95% CIs: 3.31–4.25, P < .001) as measured by the Numerical Rating Scale (NRS) and Visual Analog Scale (VAS), respectively. Disability also relieved significantly after treatment compared with that measured before treatment. The MD was 18.2 (95% CIs: 12.22–24.17, P < .001) as measured by the Oswestry Disability Index (ODI). Seventy-two percent of the patients presented positive results as measured by the Global Perceived Effect (GPE). The OR was 0.01 (95% CIs: 0.00–0.05, P < .001). Only mild complications were observed in the 7 studies, including transient hip pain, soreness, and numbness. Conclusion: C ooled radiofrequency procedure can significantly relieve pain and disability with no severe complications, and majority of patients are satisfied with this technique. Thus, it is safe and effective to use this procedure in managing patients with chronic SIJ pain. More high-quality and large-scale randomized controlled trials (RCTs) are required to validate our findings. Limitations: The sample size of the included studies was small and various heterogeneity existed.